Studi Literatur tentang Perilaku Masyarakat dalam Pencegahan Malaria - Sabneno, Ade Shianti; Junias, Marylin Susanti (Innovative: Journal Of Social Science Research, 2025)
Malaria is an infectious disease that is of global concern. Malaria can be transmitted through the bite of a female Anopheles mosquito. According to global data, there will be 249 million cases of malaria in 2022. Meanwhile, the estimated number of deaths due to malaria in 2022 will reach 608,000. Indonesia is one of nine malaria endemic countries in the Southeast Asia region which contributes around 2% of the country's global malaria burden. The aim of the research is to determine the behavior of Indonesian people in preventing malaria. The method in this research is literature study. The author can conclude that there is an impact or influence on community behavior on Malaria prevention. Malaria can be prevented and controlled with vector control efforts and appropriate management of malaria cases such as cleaning the environment, awareness of using mosquito nets regularly, wearing closed clothing when going out at night or using anti-mosquito lotion. Community behavior plays a key role in the success of preventing malaria. The level of community knowledge, attitudes and practices towards malaria greatly determines the effectiveness of various preventive interventions, such as the use of insecticide-treated bed nets, environmental management and access to health services. Effective interventions such as increasing public education, distribution of prevention tools such as insecticide-treated bed nets, environmental management and community empowerment are urgently needed to increase awareness and preventive behavior.